Wikipedia, Work and Capitalism : A Realm of Freedom? - Lund, Arwid (Dynamics of Virtual Work, 2017)
This book relates Wikipedians' conceptions of their activities in terms of play, game, work and labour, to their views on Wikipedia and capitalism. The author identifies and compares ideology formations with each other, and with contemporary Marxist theory, providing critical evaluation of the perceived economic relation between peer production and capitalism. The book covers a range of topics including encyclopaedias and the digital revolution; Marxist approaches to cognitive capitalism; and crowdsourcing. The book richly contributes to the emerging literature of critical internet studies, providing a unique intersection of three fields of knowledge: social effects of digital technology; ideologies and politics of cognitive capitalism's social relations; and the culture of contemporary capitalism. Wikipedia, Work and Capitalism will be of interest to students and scholars across a range of disciplines including political economy, sociology and digital cultures, as well as social activists, Wikipedians, and peer producers. .